Genetic characteristics of Panax vietnamensis Ha & Grushv. populations based on ssr - Mai, Nguyen Thi Hong; Son, Le Thanh; Trang, Nguyen Thi Phuong (Academia Journal of Biology, 2020)
The results of genetic analysis of two Panax vietnamensis populations, collected in Tac-ngo ginseng garden, Tra Linh commune, Quang Nam Province and Mang ri ginseng garden, Kon Tum Province, showed that the population of ngoc linh ginseng in Quang Nam has higher alen frequency compared to the Ngoc Linh ginseng population in Kon Tum (AR = 2.27 > AR = 2.05). The population of ngoc linh ginseng in Quang Nam has the expected heterozygous frequency (He) higher than the expected heterozygous frequency of the ginseng population in Kon Tum (0.42 > 0.4). The observed heterozygous frequency (Ho) of the ngoc linh population in Quang Nam was also higher than the observed heterozygous frequency compared to the ngoc linh ginseng population in Kon Tum (0.49 > 0.43). These results demonstrated that both populations of ngoc linh ginseng in Quang Nam and Kon Tum are maintaining high heterozygous frequencies; self-pollination has not affected to the genetic structure of these both populations yet. However, the population of ngoc linh ginseng in Quang Nam showed a higher level of diversity and heterozygous frequency than the ngoc linh ginseng population in Kon Tum.